News or innovations in neonatal surgery - Giorgia Totonelli; Francesco Morini; Pietro Bagolan (Hygeia Press di Corridori Marinella, 2015)
Over the last decades, because of the development of several clinical and technological advances, there has been a revolution in the management of neonatal and pediatric patients. These progresses reported an improvement in the survival rate of extremely ill neonates, who now have the chance to survive into adulthood. The intent of this review is to highlight not only the advances obtained in the neonatal surgery, but also the results of a multidisciplinary work focused on the fetus, preterm and newborn baby with a surgical anomaly or disease. Attention is also paid to the recent tendency to share knowledge, protocols and database out of the single Institution or country and to follow these delicate and fragile neonatal patients to the adulthood, developing the transitional care.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)